TO KNOW RETHINK THEM OF THE PHYSICAL EDUCATION: THE ATHLETICS AS CONTENT IN THE BASIC EDUCATION (Fiep Bulletin - online, 2013)
The Physical Education as area of knowledge, knowledge understood here not as the accomplishment of a pure motor action and simply, more yes, the understanding and learning of this motor action. To understand the reason and as of this to put into motion disciplines, it of Physical Education will have to change its performance inside of the school for a new conception, that is the knowledge of the motricidade human being, inside of a conception of transcendência of this to put into motion. However when we deal with lesson of Physical Education, we verify that these subjects possess a vast amplitude very. We look for, thus, to present the cultural manifestation sport, and inside of this we will approach the Atletismo content. For this, we must be conscientious that all the MOTRICIDADE Corporal Culture Cultural Manifestations and Capacitativa Structures SPORTS Athletics content that we will go to teach necessarily will have to be part of the reality of our pupils. When we start to analyze the content in this way we can inquire that our pupils already turn some thing, in the television in another media something related to the atletismo. As component cultural, the atletismo must be studied by means of a historical survey. When the pupils start to understand why this modality was created and systemize, the beginning of the understanding is being made possible. This historical knowledge, makes possible to the pupil the understanding of the cultural construction of a modality and its development through the time until arriving nowadays. With the concluded historical development, it now fits the experience and understanding of the tests, and depleted the tests, we leave then for the use of this modality as half to reach other contents, in such a way, the Athletics passes to be conceived as metodológy procedure. Exactly if treating to a esportiva modality, our content can and must very advance beyond the accomplishment of the gesture technician.
Keywords: Athletics; Content; Physical Education